2018
DOI: 10.1177/0969141318806322
|View full text |Cite
|
Sign up to set email alerts
|

Testing active choice for screening practitioner’s gender in endoscopy among disinclined women: An online experiment

Abstract: Objectives A large proportion of women have a preference for a same-gender endoscopy practitioner. We tested how information about practitioner gender affected intention to have bowel scope screening in a sample of women disinclined to have the test. Methods In an online experimental survey, women aged 35–54 living in England who did not intend to participate in bowel scope screening (N = 1060) were randomised to one of four experimental conditions: (1) control (practitioner’s gender is unknown), (2) opposite-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
(23 reference statements)
0
14
0
1
Order By: Relevance
“…Those who had indicated that they would probably or definitely have the test, were redirected to the study briefing and final survey page where they were thanked for their participation. Those who stated that they would definitely or probably not do the screening test were individually randomised, with equal probability, to one of two conditions [ 35 ].…”
Section: Studymentioning
confidence: 99%
“…Those who had indicated that they would probably or definitely have the test, were redirected to the study briefing and final survey page where they were thanked for their participation. Those who stated that they would definitely or probably not do the screening test were individually randomised, with equal probability, to one of two conditions [ 35 ].…”
Section: Studymentioning
confidence: 99%
“…Specifically, we wanted to compare verbal quantifiers to a precise numerical norms message and a control condition without any information about normative screening behaviour. In line with previous experimental studies [17, 22, 23], we focused on individuals who initially expressed little or no interest in BSS, to minimise ceiling and social desirability effects often associated with self-reported intention measures. [24] We also wanted to simulate a targeted intervention aimed at non-attenders who are in most need of an effective behavioural intervention.…”
Section: Introductionmentioning
confidence: 99%
“…We report the reduced models in the tables and the full models in the supplementary table. In line with previous experiments with similar designs, we used complee case analysis and did not impute missing data for two reasons (Stoffel et al, 2018;2019a, 2019b, 2019cvon Wagner et al, 2019). Firstly, as in the experiment all the questions were mandatory, there were no single missing responses, but rather survey abandonment.The analysis of the response behaviour did not reveal specific abandonment behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…A randomised online experiment was designed to measure the effect of appointment choice set size on intention to confirm the screening appointment. Following previous studies, in 2018, a survey company (ResearchNow) invited men and women from their online panel to take part in a survey on BSS if they were aged 35-54 years, living in England, without a previous diagnosis of bowel cancer (Stoffel et al, 2018(Stoffel et al, , 2019a(Stoffel et al, , 2019b2019c;von Wagner et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation